Analisis Kebijakan Penyertaan Modal Pemerintah Daerah Terhadap Kinerja Perusahaan Umum Daerah Air Minum Pancuran Telago Kabupaten Bungo - Wineh, Sri (Media Ekonomi, 2021)
This study aims to determine how much the equity participation of the Local Government in Telago Pancuran Water Supply Company and to determine the impact of the local goverment capital participation on the performance of the Telago Pancuran Water Supply Company. The object of research is the Telago Pancuran Water Supply Company, with a research period of five years, namely 2015 to 2019. The data collection technique uses observation, interview and documentation methods. The data analysis technique in this research uses quantitative methods using financial performance formulas, Return on Equity, operating ratios, cash ratios and billing effectiveness. The results of this study indicate that the amount of equity participation of the local Government to the Telago Pancuran Water Company continues to increase until 2016, for 2017 to 2019 it has decreased. Meanwhile, the impact of equity participation on company performance can be seen in the Return on Equity ratio, operating ratio, cash ratio for collection effectiveness.